Microfinance and poverty alleviation - Irobi, Nnenna Christiana (2008)
Microfinance, which is one of the tools used in poverty alleviation, has been with us since time immemorial. In Nigeria it is traditionally rooted, while providing credit and financial services to the poor or low-income earners. There are people with self-help groups, rotating savings and associations with several activities aiding members to come out of poverty etc. Microfinance however, is been implemented to overcome the failure of the formal banking industry at offering small loans for the poor to enable them perform some income generating activities. The question of 'whom does the microfinance benefit', and how it affects the welfare of different groups of individuals and household was tackled in this study. This was achieved through studying the impact of micro financing on a group of women - Obazu Progressive Women Association, Mbieri, Owerri in Nigeria involved in poverty alleviating activities for their members.